Peran Penting Digital Marketing dalam Pertumbuhan UMKM - Muhammad Rizky; Rafli Alhafizh; Rian Abdul Rohman; Resdy Isra Firdaus; Siti Anggia Denisa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy but still face numerous challenges in enhancing their competitiveness in the digital era. Digital marketing serves as a key strategy in expanding market reach and improving promotional efficiency. This study aims to explore the role of digital marketing in supporting MSME growth through a case study of the Merdeka Belajar Kampus Merdeka (MBKM) program implemented in Sukamaju Village, Majalaya District, Bandung Regency. This research employs a qualitative approach, utilizing observations and interviews with MSME actors who participated in digital marketing training. The activities included socialization, seminars, and direct mentoring on utilizing social media, marketplaces, and engaging promotional content creation. The findings reveal that the digital marketing training program positively impacted the understanding and skills of MSME actors in leveraging digital technology. A total of 27 seminar participants expressed high interest in implementing digital marketing strategies in their businesses. Additionally, direct mentoring helped MSME actors formulate more effective promotional strategies.